2018
DOI: 10.15386/cjmed-840
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Psychological Stress in Recurrent Aphthous Stomatitis Among Female Dental Students in Saudi Arabia

Abstract: IntroductionRecurrent Aphthous Stomatitis (RAS) is a common oral mucosal disorder which is characterized by recurrent ulcerations mainly confined to non-keratinized oral mucosa. Though the exact etiology is imprecise, stress and anxiety were found to be linked with the onset of RAS. The present study was directed to know the prevalence of RAS among female dental students in King Khalid University, to find out the association between RAS and psychological stress and the effectiveness of Hospital Anxiety and Dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 13 publications
1
36
1
Order By: Relevance
“…The highest rates of anxiety disorder among patients with RAS was reported by Ajmal et.al. 16 They reported 88% of the female dental students were suffering from anxiety, which was far off distant compared with the nding of this study. Notably, a study from Croatia registered the lowest prevalence of anxiety, 26.5%.…”
Section: Anxiety Associated With Rascontrasting
confidence: 46%
See 3 more Smart Citations
“…The highest rates of anxiety disorder among patients with RAS was reported by Ajmal et.al. 16 They reported 88% of the female dental students were suffering from anxiety, which was far off distant compared with the nding of this study. Notably, a study from Croatia registered the lowest prevalence of anxiety, 26.5%.…”
Section: Anxiety Associated With Rascontrasting
confidence: 46%
“…Incidence of depression among dental students in this study was high (62.5%). The prevalence of depression among patients with RAS had also been discussed 16,17,18 . Ajmal et.al.…”
Section: Depression Associated With Rasmentioning
confidence: 99%
See 2 more Smart Citations
“…In this cross-sectional study, we explored the distribution of RAS, dietary factors, self-reported trigger factors, and therapeutic methods among a study population from Nanjing and reported a prevalence of 21.4% in accordance with the literature [14,24,25]. Moreover, less than half (72, 44.7%) of them had ever received treatment for RAS, which was lower than the percentage reported in another study [21,26], and nearly one-third participants who have ever treated RAS mainly use ATs instead of conventional medicine, despite a lack of randomized controlled trials to prove the effectiveness and safety of these ATs.…”
Section: Discussionmentioning
confidence: 67%